Large-scale reservoir modeling of the Vendenheim geothermal site (France) - J. Abreu-Torres; G. Hutka; G. Hutka; G. Blöcher; G. Blöcher; M. Cacace; V. Magnenet; J. Schmittbuhl (Advances in Geosciences)
During the Vendenheim deep geothermal project (Strasbourg Eurometropole, France), large induced seismic events led to the arrest of the project. Two important features of the induced seismicity were unexpected: the large distance to the wells of a cluster of seismic events (4–5 km) and the occurrence of the largest event Mlv3. 9 at the bottom of the wells, six months after shut-in. To better understand the natural hydro-thermal conditions at the Vendenheim site, we develop within the framework of the DT-GEO project (Horizon Europe) a simplified large-scale model (8 km × 8 km × 6 km) of the area. We aim at performing in-silico experimentation to reproduce the natural hydrothermal state of the geothermal reservoir related to the heat flow (conductive/convective) within the model. We first test our methods by solving 2D and 3D benchmarks related to the convective regime in saturated porous media. Our model is based on the MOOSE/GOLEM framework (finite element approach) and integrate the public regional geological model GEORG that includes major lithologies. We present the coarse-grained simulations of the natural fluid circulation.